2018
DOI: 10.1186/s40104-017-0226-9
|View full text |Cite
|
Sign up to set email alerts
|

Xylose: absorption, fermentation, and post-absorptive metabolism in the pig

Abstract: Xylose, as β-1,4-linked xylan, makes up much of the hemicellulose in cell walls of cereal carbohydrates fed to pigs. As inclusion of fibrous ingredients in swine diets continues to increase, supplementation of carbohydrases, such as xylanase, is of interest. However, much progress is warranted to achieve consistent enzyme efficacy, including an improved understanding of the utilization and energetic contribution of xylanase hydrolysis product (i.e. xylooligosaccharides or monomeric xylose). This review examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 69 publications
2
30
0
Order By: Relevance
“…They were found to lose the capability to utilize l -arginine as a sole carbon source under anaerobic conditions due to the absence of the succinylglutamic semialdehyde dehydrogenase ( astD ) and l -xylulose in both aerobic and anaerobic conditions due to the absence of three genes ( yiaMNO ). l -xylose is an upstream precursor of l -xylulose and is abundant in the hemicellulose walls of the cereals fed to pigs 21 . It was shown to be excreted in high proportions in the urine indicating very low levels of xylose absorption 21 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were found to lose the capability to utilize l -arginine as a sole carbon source under anaerobic conditions due to the absence of the succinylglutamic semialdehyde dehydrogenase ( astD ) and l -xylulose in both aerobic and anaerobic conditions due to the absence of three genes ( yiaMNO ). l -xylose is an upstream precursor of l -xylulose and is abundant in the hemicellulose walls of the cereals fed to pigs 21 . It was shown to be excreted in high proportions in the urine indicating very low levels of xylose absorption 21 .…”
Section: Resultsmentioning
confidence: 99%
“…l -xylose is an upstream precursor of l -xylulose and is abundant in the hemicellulose walls of the cereals fed to pigs 21 . It was shown to be excreted in high proportions in the urine indicating very low levels of xylose absorption 21 . The loss of yiaMNO may have occurred because l -xylulose is not available in the swine extraintestinal environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results of digestibility and energy value, it needs to be further explained that the nutrient digestibility and the ME values are not completely related. Fermentation of DF is a less efficient means to release dietary energy to pigs compared with direct absorption and oxidation of starch, fat and protein (Huntley & Patience, 2018). Noblet and van Milgen (2004) reported that energetic efficiency ofDF (60%) is lower than that TA B L E 8 Effect of sunflower meal (SFM) and body weight (BW) of pig on the digestible energy (DE), metabolizable energy (ME) and the apparent total tract digestibility (ATTD) of nutrients in Exp.…”
Section: Effect Of Body Weight Of Pigs On Attd Of Nutrient and Enermentioning
confidence: 99%
“…In a study with volunteers, 70% of the dose was absorbed (Craig and Ehrenpreis, 1999). A part of D-xylose also reaches the colon, where it is metabolised by gut bacteria (Huntley and Patience, 2018). After intravenous infusion of 20 g 14 C-xylose to one human, 13.5% of the dose was detected in expired CO 2 .…”
Section: 8mentioning
confidence: 99%